PROBLEMATIKA, PERANAN DAN FUNGSI PERENCANAAN PENDIDIKAN DI INDONESIA - Suhada Suhada (Andragogi: Jurnal Pendidikan Islam dan Manajemen Pendidikan Islam, 2020)
This research is a literature study related to problems, the role and function of education planning in Indonesia. Data collection was carried out through various sources that can be used in relation to the problems of Islamic multicultural education in Indonesia. In searching some literature using a search engine or maybe it is easier to index any type of document. For example, we use Google Scholar with a query containing Social Network clauses, of course the number of clauses will be generated with a list of related documents. The conclusion in this study is that the existence of problems in education in Indonesia also causes constraints in education planning in Indonesia. The education system in Indonesia must be planned by considering various things. Planning is an activity to see the future in terms of determining policies, priorities and costs of education by prioritizing the existing realities in the economic, social and political fields to develop the state education system and students served by this system. This means that in planning the national education system must consider economic, social, political and cultural factors. The education system in our country has undergone many changes, this may be due to educational planning that does not understand the aspects involved in it, so that our national education system is unable to match the conditions of Indonesian society and the resulting graduates are not relevant to the needs of the workforce. This makes it difficult for our country's human resources (HR) to compete with foreign human resources. The functions and roles of educational planning are as follows: 1) As a guide for the implementation of educational development activities. 2) As a means of controlling the implementation of education development. 3) As a tool to ensure the quality of educational development. 4) As a means of achieving educational goals effectively and efficiently. 5) As a means to ensure the smooth achievement of educational development goals. 6) As a means of clarifying the vision, mission and strategy of education development. 7) As a logical and systematic tool to change the education system for the better.